The Effect Of Compensation, On Performance, Motivation And Work Achievement On Non-Permanent Teachers: Case Study at SDN Malingping, Cisitu District, Sumedang Regency - Muhammad Irfan Nur’Ari (SINTESA, 2022)
This study aims to determine the factors that affect the performance of Non-Permanent Teachers (GTT) at SDN Malingping. These factors are the influence of compensation and work motivation. Teachers who have high work motivation will have a positive impact on institutions in the school environment, so that these goals can be achieved. In this study, there are 2 problems, namely the effect of compensation on work motivation of non-permanent teachers (GTT) at SDN Malingping. This study uses qualitative methods, the data collection techniques used are document analysis and observation. Teachers are Human Resources (HR) which are very important for human life because teachers have an important role in the intellectual life of the nation. However, there are many conflicts that occur in Non-Permanent Teachers (GTT). Non-Permanent Teachers (GTT) are required to work optimally so that their students can become the next generation of quality. However, Non-Permanent Teachers (GTT) do not receive proper rights. This can lead to a prolonged dilemma, the magnitude of the responsibility given as teaching staff has not been accompanied by the commensurate rights received by Non-Permanent Teachers (GTT). The number of demands and workloads borne by non-permanent teachers (GTT) can lead to compensation, motivation and work performance and work stress.